Acupuncture and related therapies for the anxiety and depression in irritable bowel syndrome with diarrhea (IBS-D): A network meta-analysis of randomized controlled trials - Wang, Xuesong; Shi, Xuliang; Lv, Jing; Zhang, Juncha; Huo, Yongli; Zuo, Guang; Lu, Guangtong; Liu, Cunzhi; She, Yanfen (Frontiers in Psychiatry, 2022)
Objective A growing number of clinical studies have suggested the value of acupuncture-related therapies for patients with irritable bowel syndrome with diarrhea (IBS-D), and the patient’s mental state plays an important role, but there are many types of acupuncture-related therapies involved. This study aimed to evaluate the mental status, efficacy and safety of the different acupuncture-related therapies for IBS-D patients. Methods We searched seven databases to collect randomized controlled trials of acupuncture-related therapies for IBS-D. After independent literature screening and data extraction, the quality of the final included literature was evaluated. Hamilton anxiety rating scale (HAMA), hamilton depression rating scale (HAMD), self-rating anxiety scale (SAS), and self-rating depression scale (SDS) was used as the primary outcome indicator. And the network meta-analysis (NMA) was performed by using Revman 5.4, Stata 15.0 and WinBUGS 1.4.3 software, and the surface under the cumulative ranking curve was conducted to rank the included interventions. Results We analyzed 24 eligible studies with 1,885 patients, involving eight types of acupuncture and related therapies along with comprehensive therapies. The NMA result shows that: for SAS scores, combined therapies were more efficacious than anti-diarrheal or antispasmodic (western medicine, WM) (SMD: −8.92; 95% CI: −15.30, −2.47); for SDS scores, combined therapies were more efficacious than WM (SMD: −8.45; 95% CI: −15.50, −1.41). For HAMA scores, moxibustion (MOX) was more efficacious than placebo (SMD: −8.66; 95% CI: −16.64, −0.38). For HAMD scores, MOX was more efficacious than all other included interventions. For response rate, MOX was more efficacious than the following interventions: acupuncture (ACU) (SMD:0.29; 95% CI:0.08,0.93), Chinese herb medicine (CH) (SMD:0.09; 95% CI:0.02,0.36), combined therapies (SMD:0.23; 95% CI:0.06, 0.85), electroacupuncture (EA) (SMD:0.06; 95% CI:0.01,0.33), warm acupuncture (WA) (SMD:22.16; 95% CI:3.53,148.10), WM (SMD:15.59; 95% CI:4.68,61.21), and placebo (SMD:9.80; 95% CI:2.90,45.51). Combined therapies were more efficacious than the following interventions: CH (SMD:0.39; 95% CI:0.19,0.80), WA (SMD:4.96; 95% CI:1.30,21.62), and WM (SMD:3.62; 95% CI:2.35,5.66). The comprehensive ranking results show that MOX, ACU, combined therapies, and EA had high SUCRA rankings involving different outcome indicators. Conclusion MOX, ACU, combined therapies, and EA better alleviate anxiety and depression among IBS-D patients, and with a higher safety level, may be the optimal therapies. In addition, combining acupuncture-related treatments and other therapies also delivers a higher global benefit level. Systematic review registration [https://www.crd.york.ac.uk/], identifier [CRD42022364560].